A Tax‐Tax Clientele for Inde‐linked Bonds: A Comment - KNOLL, MICHAEL S. (Journal of Finance, 1991)
ABSTRACT This comment describes the U.S. federal income tax treatment of corporate bonds that are indexed for inflation and argues that these bonds do not have a tax‐tax clientele in the United States.